PRINCIPAL COMPONENT ANANLYSIS OF AIR PARTICULATE DATA FROM THE INDUSTRIAL AREA OF ISLAMABAD, PAKISTAN - Waheed, S.; Siddique, N.; Daud, M. (The Nucleus, 2020)
A Gent air sampler was used to collect 72 pairs of size fractionated coarse and fine (PM10 and PM2.5) particulate mass samples from the industrial zone (sector 1-9) of Islamabad. These samples were analyzed for their elemental composition using Instrumental Neutron Activation Analysis (INAA). Principal component analysis (PCA), which can be used for source apportionment of quantified elemental data, was used to interpret the data. Graphical representations of loadings were used to explain the data through grouping of the elements from same source. The present work shows well defined elemental fingerprints of suspended soil and road dust, industry, motor vehicle exhaust and tyres, and coal and refuses combustions for the studied locality of Islamabad.